Microbial dysbiosis in cholangiocarcinoma - Liu, Yunjia; Huang, Shaohui; Zhang, Yang; Zhang, Yuankun; Xu, Yunfei; Tang, Yongchang; Guo, Sen; Zhang, Zongli (Frontiers in Microbiology, 2026)
Cholangiocarcinoma (CCA) is a highly aggressive malignancy of the biliary epithelium, with its incidence and mortality rates continuing to rise worldwide. Advances in high-throughput sequencing and metabolomic technologies have intensified interest in elucidating the role of the microbiome in CCA. Microbial dysbiosis may contribute to tumor initiation and progression by inducing chronic inflammation, altering metabolic pathways, and modulating the immune microenvironment. Moreover, these microbial alterations have been associated with therapeutic resistance, underscoring their potential impact on disease progression and treatment outcomes. This review summarizes the potential origins of intratumoral microorganisms and the microbiome alterations associated with distinct CCA subtypes. Crucially, we critically evaluate the methodological challenges inherent to low-biomass biliary samples—including contamination risks and confounding factors such as cholestasis and medical interventions—and distinguish between associative and causal evidence in current literature. Collectively, this work aims to provide a rigorous theoretical framework and novel insights for microbiome-based strategies in the early diagnosis and treatment of CCA.